2021
DOI: 10.3389/fcvm.2021.646402
|View full text |Cite
|
Sign up to set email alerts
|

Association of N-Terminal Pro-brain Natriuretic Peptide With Volume Status and Cardiac Function in Hemodialysis Patients

Abstract: Introduction: N-terminal-pro-brain natriuretic peptide (NT-pro BNP) is secreted by cardiomyocytes in cases of cardiac structure disorder and volume overload. However, the relationship between NT-pro BNP level and body fluid status in dialysis patients with reduced cardiac ejection function (EF) is uncertain. Therefore, we aimed to investigate this relationship.Methods: We enrolled patients who had been receiving hemodialysis for >3 months. Blood sample, transthoracic echocardiographic, and bioimpedance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 35 publications
1
10
1
Order By: Relevance
“…Moreover, we planned to analyze the correlation by measuring NT-proBNP and BIS-OH in dry weight (less overhydration status) after HD. In the previous study [11], because BIS and NT-proBNP were measured on a midweek non-dialysis day, the volume status of the patients was overestimated compared to our study, and the variability of OH was large (OH: 2.68 [−1.9-12.2] vs. 0.4 [−0.7-1.5]). Although NT-proBNP decreased after dialysis, enrolled patients used the same dialyzer and dialysis machine.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…Moreover, we planned to analyze the correlation by measuring NT-proBNP and BIS-OH in dry weight (less overhydration status) after HD. In the previous study [11], because BIS and NT-proBNP were measured on a midweek non-dialysis day, the volume status of the patients was overestimated compared to our study, and the variability of OH was large (OH: 2.68 [−1.9-12.2] vs. 0.4 [−0.7-1.5]). Although NT-proBNP decreased after dialysis, enrolled patients used the same dialyzer and dialysis machine.…”
Section: Discussioncontrasting
confidence: 80%
“…Because volume overload in ESKD patients can lead to systemic hypertension and HF [ 9 ], it is important to properly evaluate volume status. NT-proBNP could be helpful for monitoring excess fluid volume and dry weight [ 10 , 11 , 12 ]. However, kidney function has an inverse correlation with NT-proBNP level [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors found significant associations between OH/AEC and higher NT-proBNP levels. Likewise, Wang et al ( 37 ) evaluated 129 HD patients and reported an association between NT-proBNP levels and hyperhydration assessed by BCM, concluding that the BIS is a reliable marker of volume status.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Wakabayashi et al found that cardiac function can get better by controlling dry body weight even in HD patients with high AVF blood flow [35]. A recent study by Wang et al on 129 HD patients documented the predictive value of NT-pro-BNP in the assessment of volume overload in hemodialysis patients with or without EF declines [36]. Baki et al found that combined elevation of BNP level and decreased IVC collapsibility index were sensitive markers for subclinical volume overload detection in CKD patients [37].…”
Section: Discussionmentioning
confidence: 99%